Selenium metabolism in rats after administration of toxic doses of selenite - Ostádalová, I; Babický, A; Kopoldová, J (Physiologia Bohemoslovaca, 1988)
We studied organ concentration, excretion and excreted forms of selenium in young and adult rats after a single s.c. injection of a sublethal dose of 75Se-selenite. In the young about a 10-fold higher concentration of 75Se in blood, liver, kidneys and In the young, about a 10-fold higher concentration of 75Se in blood, liver, kidneys and heart was found at all the experimental intervals studied (1-7 days). The highest 75Se concentration in the young was in the liver while in the adults it was found in the kidneys. The spectrum of radioselenium metabolites in the urine was the same in both groups. However, the main product excreted by young rats was 75Se-glutathione selenotrisulphide and an unidentified neutral substance while it was the trimethylselenonium ion in the adults. Ontogenetic differences in selenium metabolism could be one of the factors underlying the differences in the response of the young and the adult rats to toxic doses of selenite.
Keywords: Aging; tkáňová distribuce; selen; Selenious Acid; Rats; Selenium Radioisotopes; radioizotopy selenu; Animals; Male; inbrední kmeny potkanů; Rats, Inbred Strains; Tissue Distribution; zvířata; kyselina seleničitá; mužské pohlaví; stárnutí; Selenium; krysa rodu Rattus